Pengaruh Inovasi Produk dan Inovasi Yang Akan Datang terhadap Keputusan Pembelian Konsumen Studi Kasus: Konsumen Telepon Selular Nokia - Haryanto, Jony Oktavian; Polluan, Jeane (Jurnal Widya Manajemen & Akuntansi, 2007)
Product innovation is an important element in customer buying decision for high technology product including mobile phone. Therefore, it is quite important to know the role of product innovation in customer buying decision. The purpose of this research is to identify the effect of product innovation, forthcoming innovation , and preference to delay present purchase on customer buying decision. This research found that both product innovation and preference to delay purchase influence customer buying decision positively. Moreover, product influences the forthcoming innovation positively as well as affects customer preference to delay purchase. On the other hand, the forthcoming innovation influences customer buying decision negatively.